Full phenology cycle carbon flux dynamics and driving mechanism of Moso bamboo forest - Xu, Cenheng; Mao, Fangjie; Du, Huaqiang; Li, Xuejian; Sun, Jiaqian; Ye, Fengfeng; Zheng, Zhaodong; Teng, Xianfeng; Yang, Ningxin (Frontiers in Plant Science, 2024)
Moso bamboo forests, widely distributed in subtropical regions, are increasingly valued for their strong carbon sequestration capacity. However, the carbon flux variations and the driving mechanisms of Moso bamboo forest ecosystems of each phenology period have not been adequately explained. Hence, this study utilizes comprehensive observational data from a Moso bamboo forest eddy covariance observation for the full phenological cycle (2011-2015), fitting a light response equation to elucidate the evolving dynamics of carbon flux and photosynthetic characteristics throughout the entire phenological cycle, and employing correlation and path analysis to reveal the response mechanisms of carbon flux to both biotic and abiotic factors. The results showed that, First, the net ecosystem exchange (NEE) of Moso bamboo forest exhibits significant variations across six phenological periods, with LSOFF demonstrating the highest NEE at -23.85 ± 12.61 gC·m⁻2·5day-1, followed by LSON at -19.04 ± 11.77 gC·m⁻2·5day-1 and FGON at -17.30 ± 9.58 gC·m⁻2·5day-1, while NFOFF have the lowest value with 3.37 ± 8.24 gC·m⁻2·5day-1. Second, the maximum net photosynthetic rate (Pmax) and apparent quantum efficiency (α) fluctuated from 0.42 ± 0.20 (FGON) to 0.75 ± 0.24 mg·m⁻2·s⁻1 (NFOFF) and from 2.3 ± 1.3 (NFOFF) to 3.3 ± 1.8 μg·μmol⁻1 (LSOFF), respectively. Third, based on the path analysis, soil temperature was the most important driving factor of photosynthetic rate and NEE variation, with path coefficient 0.81 and 0.55, respectively, followed by leaf area index (LAI), air temperature, and vapor pressure difference, and precipitation. Finally, interannually, increased LAI demonstrated the potential to enhance the carbon sequestration capability of Moso bamboo forests, particularly in off-years, with the highest correlation coefficient with NEE (-0.59) among the six factors. The results provide a scientific basis for carbon sink assessment of Moso bamboo forests and provide a reference for developing Moso bamboo forest management strategies.